Dental Light-Cured Polymer Nanocomposites: A Brief Review of Experimental Results Obtained from the Study of Some Physicochemical Properties - Vouvoudi, Evangelia C.; Sideridou, Irini D. (Journal of Composites and Biodegradable Polymers, 2014)
This article is a brief review of the experimental results obtained from the study of some physicochemical properties of five dental commercial light-cured nanocomposites: Filtek Supreme XT Body (FSB) and Filtek Supreme XT Translucent (FST), both characterized as nanofill composites, and Grandio (GR), Tetric EvoCeram (TEC) and Protofill-nano (PR) characterized as nanohybrid composites. The properties presented are: volumetric shrinkage due to polymerization, sorption, solubility and volume increase after sorption of composites in water or artificial saliva SAGF® medium for 30 days, flexural strength and modulus after immersion in water or artificial saliva for one or 30 days and finally the dynamic mechanical properties (storage modulus E', loss modulus E'', tand=E''/E' and Tg) determined 1h after light-curing or after immersion in an oral/food simulating liquid (water, artificial saliva or ethanol/water solution 75%vol) for 1 month. It was found via physicochemical properties that the most corrosive solvent is EtOH which heavily affects the polymeric matrix, while water and saliva are smoother media. Moreover, the more rigid and concrete polymeric chains may sustain higher load during mechanical tests, so that the composites with stronger networks shall demonstrate resistance.